Association of serum hormone profile and semen quality of infertile males in and around Chennai - Palani, K.; Jabbar, A. Abdul; Jagannathan, N.; Thangadurai, T. Babu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The infertility rate in India has also increased gradually along with population growth. Based on the geographic, the prevalence of male infertility varies. It is noticed that around the world 60–80 million couples with infertility problem every year. The aim of the study was to assess the correlation between the serum hormones and semen quality in infertile males. Methods: This research study was conducted in 60 infertile males aged from 20–50 years who reported at the Department of Andrology, Kanmani Fertility Centre (Pvt. Ltd.), Chennai, Tamil Nadu, India. The semen and hormone analysis was done in all study participants and its correlation was studied using SPSS (statistical product and service solutions) software. Results: The results demonstrate that among the study participants, 15.0% of them were normozoospermia, asthenozoospermia (26.6%), asthenoteratozoospermia (21.6%), oligoasthenozoospermia (16.6%) and oligoasthenoteratozoospermia (20.0) respectively. The results of Pearson correlation revealed that TSH, FSH, LH and PRL show a negative correlation but TST level shows a positive correlation with semen parameters. Conclusions: This study concludes that the serum hormones concentration was observed abnormal in infertile males which show negative correlation with semen parameters of the study participants.